Comparative analysis of SRAM cell with leakage power reduction approaches - Paradhasaradhi, Damarla; Jaya Lakshmi, Kollu; Harika, Yadavalli; Ravi Teja Sai, Busa; Jayanth Krishna, Golla (International Journal of Engineering and Technology, 2018)
In deep sub-micron technologies, high number of transistors is mounted onto a small chip area where, SRAM plays a vital role and is considered as a major part in many VLSI ICs because of its large density of storage and very less access time. Due to the demand of low power applications the design of low power and low voltage memory is a demanding task. In these memories majority of power dissipation depends on leakage power. This paper analyzes the basic 6T SRAM cell operation. Here two different leakage power reduction approaches are introduced to apply for basic 6T SRAM. The performance analysis of basic SRAM cell, SRAM cell using drowsy-cache approach and SRAM cell using clamping diode are designed at 130nm using Mentor Graphics IC Studio tool. The proposed SRAM cell using clamping diode proves to be a better power reduction technique in terms of power as compared with others SRAM structures. At 3.3V, power saving by the proposed SRAM cell is 20% less than associated to basic 6T SRAM Cell.